Diagnostic and Prognostic Value of CEA and CA19-9 in Colorectal Cancer - Lakemeyer, Leilani (Diseases, 2021)
Colorectal cancer (CRC) is the third most common cancer worldwide. A diagnosis at early stages with enhanced screening methods is vital as metastases and recurrences increase mortality. The aim of this study was to analyze the tumor markers CEA and CA19-9 combined in correlation with diagnostics and prognosis. Therefore, 1487 patients with CRC who were diagnosed and treated between 2000 and 2015 at the University Hospital Ulm, Germany, were retrospectively evaluated. Overall and recurrence-free survival was analyzed in association with preoperative CEA and CA19-9 separately and combined and a multivariate analysis was performed. The 5-year overall survival was significantly shorter in patients with a CEA or CA19-9 level ≥200 compared to patients with an increased, but <200, or normal level (CEA: 69%/44%/7%; CA19-9: 66%/38%/8%). Patients with both tumor markers increased also showed a remarkably shorter 5-year survival rate (CEA+/CA19-9+: 23%). The multivariate analysis emphasizes these results (p-value < 0.0001). Patients with both tumor markers elevated had the shortest 5-year recurrence-free survival rate, followed by patients with either CEA or CA19-9 elevated (CEA-/CA19-9-: 79%; CEA+/CA19-9; CEA-/CA19-9+: 65%; CEA+/CA19-9+: 44%). In conclusion, measuring CEA and CA19-9 preoperatively in CRC patients is reasonable and could be useful as a prognostic factor.